THE CONTRIBUTION MADE BY T.E. LAWRENCE TO THE THEORY OF REVOLUTIONARY WARFARE - Barron, G.K.B. (Scientia Militaria - South African Journal of Military Studies, 2012)
Lawrence was basically an academic thrown into the hurly-burly of leading an Arab revolt against Turkish domination. It could be said that the war in the Middle East was a sideshow of the First World War and Lawrence’s part was a ’ ... sideshow to the sideshow’l) Why then has Lawrence been remembered when greater military men have been forgotten? The romanticism of his exploits are surely the reason, and yet the fact that he is the first modern theorist and possibly the "father" of modern revolutionary warfare, tends to be forgotten.